Paliativní péče v nefrologii - Szonowská, Barbora (Casopis lekaru ceskych, 2018)
Despite the advances in dialysis technology over the past decades, patients with advanced chronic kidney disease (CKD) have a high symptom burden, shortened survival and substantial physical, emotional and spiritual suffering. Number of frailty patients with advanced chronic kidney disease is growing and for many of them the beginning or continuation of dialysis is associated with a high risk of short-term mortality or worsening of functional status. Identifying these fragile patients and integrating palliative care into standard nephrological care improves patients quality of life and has the potential to prolong their lives without demanding dialysis treatment. Nephrologists basic skills should include: estimating the prognosis, communication with the patient on advance care planning including end-of-life issues and consistent symptom management. In fragile patients with advanced chronic kidney disease, the disease-oriented model with quantitative targets is no longer an adequate approach to care.
Keywords: Renal Dialysis; advance care planning; paliativní péče; shared-decision making; lidé; conservative management; nefrologie; chronické selhání ledvin; Palliative Care; Humans; Quality of Life; palliative/supportive care; dialýza ledvin; chronic kidney disease; Nephrology; kvalita života; palliative dialysis withdrawal from dialysis.; Kidney Failure, Chronic